2017
DOI: 10.1111/pedi.12607
|View full text |Cite
|
Sign up to set email alerts
|

Low‐grade inflammation and muscular fitness on insulin resistance in adolescents: Results from LabMed Physical Activity Study

Abstract: Higher levels of MF seem to minimize the deleterious effect of inflammation on IR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Recently, Fraser and colleagues [ 18 ], in a longitudinal study of 20 years, demonstrated that childhood MF and CRF were associated with beta cell function and insulin resistance in adulthood. Previously, our group has shown that CRF [ 15 , 16 , 39 ] and MF [ 17 , 20 , 28 ] were inversely associated with metabolic risk factors. However, in these studies, the analysis of the combined effect of adherence to a MeDiet and both fitness components on cardiometabolic health was not possible due to the small number of adolescents in the groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Fraser and colleagues [ 18 ], in a longitudinal study of 20 years, demonstrated that childhood MF and CRF were associated with beta cell function and insulin resistance in adulthood. Previously, our group has shown that CRF [ 15 , 16 , 39 ] and MF [ 17 , 20 , 28 ] were inversely associated with metabolic risk factors. However, in these studies, the analysis of the combined effect of adherence to a MeDiet and both fitness components on cardiometabolic health was not possible due to the small number of adolescents in the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Physical fitness is recognized as an independent predictor of cardiovascular disease (CVD) and adulthood mortality [ 12 , 13 ]. Physical inactivity and low physical fitness levels, particularly cardiorespiratory fitness (CRF) [ 14 , 15 , 16 ] and muscular fitness (MF) [ 17 , 18 ], have been associated with cardiovascular risk factors in adolescents, such as insulin resistance, obesity, high blood pressure, and lipid disorders, among others.…”
Section: Introductionmentioning
confidence: 99%
“…Among a sample of 1247 children ages 8-11 years old, Nystrom et al found that CRF attenuated the relationship between BMI and increased cardiometabolic risk scores, particularly in the highest BMI categories (12). Further, while increased inflammation is often associated with insulin resistance, Agostinis-Sobrinho et al demonstrated that muscular fitness minimized this association in a cohort of 529 adolescents (22).…”
Section: Protective Role For Physical Activitymentioning
confidence: 99%
“…Isometric Handgrip (12,15,22) Standing Long Jump (12,15,22) Curr Opin Endocrinol Diabetes Obes. Author manuscript; available in PMC 2020 February 01.…”
Section: Muscular Fitnessmentioning
confidence: 99%
“…Motor fitness (i.e., speed–agility), musculoskeletal fitness (MSF), and CRF are the powerful health-related fitness components in youths [1]. In particular, low CRF and low MSF are independently associated with increased cardio-metabolic risk [2,3,4,5] and mortality [6,7] in both youth and adult populations. It has been consistently reported that a higher adiposity (i.e., central abdominal or fat mass) and metabolic risk factors are associated with lower CRF and MSF levels in young people [8].…”
Section: Introductionmentioning
confidence: 99%